Assessing the Degree of Publicness in Streets - Sandeep Paul (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Streets have always been a vital source of public life in Indian cities. The advent of virtual technologies and changing urban realities, have impacted its publicness and activation. Additionally, increasing degree of publicness in privately owned public spaces poses significant reduction in street life. Hence, it is important to assess the street qualities which contribute to public life. The physical, non-physical and metaphysical qualities of street assessments will bring out the essential qualities of streets that contribute to public life in contemporary streets. This paper enquires socio-cultural and sensory aspects of street life. It would assess parameters that contribute or contradict the degree of publicness. The study would discuss and build assessments from Vikas Mehta, William H. Whyte, Henry Lefebvre and Jan Gehl’s theories and perspectives. This research would build a critical enquiry about temporality and everyday urbanism and contribute to the discussions on placemaking and tactical urbanism strategies.